Penerapan Pendekatan Arsitektur Perilaku dalam Merancang Perpustakaan Umum Guna Mendukung Kegiatan Literasi di Kota Denpasar - Nareswari Kepakisan; Frysa Wiriantari; Suardana I Nyoman Gde (Universitas Dwijendra, 2020)
The decline in statistics on public visits to the library draws attention to review. Changing patterns and lifestyles of people shift people's views about libraries. The fast-paced era of digital literacy has shifted people's interest in libraries. Increasing time and era, libraries are no longer used as a lifestyle by the community. Human behavior, which is implemented as a form of architecture, is also known to shape human behavior. The buildings that were originally designed and shaped by humans as their fulfillment will then assist the human way in living their social life and values ​​in life. The old paradigm of society towards the library is an old building that is dark, stuffy, lonely, and even haunted. Therefore it is necessary to have a study of what kind of design can captivate the hearts of today's people so that they can then apply it in an architectural design by studying the patterns and lifestyles of today's society with the aim of obtaining a library design concept that is in accordance with the lifestyle of the community (especially students) today and the reactivation of library building facilities which are increasingly disappearing from the pattern of people's lives.